Light-induced nitric oxide release from physiologically stable porous coordination polymers. Issue 34 (30th July 2015) - Kim, Chiwon; Diring, Stéphane; Furukawa, Shuhei; Kitagawa, Susumu
Abstract : A physiologically stable PCP based on titanium ions produces nitric oxide from bis- N -nitroso functionality on ligands under light irradiation. Abstract : The development of nitric oxide (NO) releasing materials has been of significant importance due to their application in cell biology and biomedicine. Besides the macromolecular scaffold dangling NO releasing moiety, porous materials have been used to host such NO releasing molecules. Here we synthesized a series of porous coordination polymers (PCPs), in which N -nitrosamine functional groups as photoactive NO donors were introduced into the framework scaffolds by post-synthetic nitrosation of amine functionalized analogous PCPs. We further demonstrated a controlled release of NO from the PCPs by light irradiation. Though isoreticular frameworks based on octanuclear clusters of titanium or aluminium ions were chosen due to their water-stability, the frameworks showed difference in stability in cell culture media; while aluminium frameworks were less stable in water and physiological media, the titanium analogue was highly stable even under physiological conditions.